2022
DOI: 10.1055/a-1838-9491
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Promoted N-Acylation of Amines with Hydrazide: An Efficient Metal-Free Amidation

Abstract: An efficient protocol for the amidation of hydrazide with amine has been developed by utilizing I2 as an oxidant under metal and base-free conditions at room temperature. N-acylation products of amines were obtained in good to excellent yield without using toxic reagents. This method is operationally straightforward and tolerates aliphatic/aromatic and primary/secondary amines with different hydrazides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…To investigate the role of hydrazide 4 as an intermediate in the process, it was independently prepared and then subjected to the oxidative conditions with KBr/Oxone which afforded amide 2a in 71% yield. Previous protocols have been reported that involve the oxidative coupling of acyl hydrazides with amines . It was reasoned that the NI was rapidly hydrolyzed to provide a hydrazide intermediate 4 which was oxidized to diazene intermediate 3 in situ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role of hydrazide 4 as an intermediate in the process, it was independently prepared and then subjected to the oxidative conditions with KBr/Oxone which afforded amide 2a in 71% yield. Previous protocols have been reported that involve the oxidative coupling of acyl hydrazides with amines . It was reasoned that the NI was rapidly hydrolyzed to provide a hydrazide intermediate 4 which was oxidized to diazene intermediate 3 in situ .…”
Section: Resultsmentioning
confidence: 99%
“…Previous protocols have been reported that involve the oxidative coupling of acyl hydrazides with amines. 20 It was reasoned that the NI was rapidly hydrolyzed to provide a hydrazide intermediate 4 which was oxidized to diazene intermediate 3 in situ . In our manifold, acyl diazene 3 is a reactive acylating agent and reacts with the requisite amine to form the amide products, with loss of nitrogen and concomitant formation of nitrobenzene as a byproduct which was detected by LC analysis ( Scheme 5 ), and confirmed via gas chromatography–MS (GC–MS).…”
Section: Resultsmentioning
confidence: 99%